Comprehensive Physiology 2012
DOI: 10.1002/cphy.c100029
|View full text |Cite
|
Sign up to set email alerts
|

High‐Altitude Pulmonary Edema

Abstract: High-altitude pulmonary edema (HAPE), a not uncommon form of acute altitude illness, can occur within days of ascent above 2500 to 3000 m. Although life-threatening, it is avoidable by slow ascent to permit acclimatization or with drug prophylaxis. The critical pathophysiology is an excessive rise in pulmonary vascular resistance or hypoxic pulmonary vasoconstriction (HPV) leading to increased microvascular pressures. The resultant hydrostatic stress causes dynamic changes in the permeability of the alveolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 213 publications
0
123
0
2
Order By: Relevance
“…However, the two major theories for the cause of HAPE, exacerbated pulmonary hypertension and/or capillary alterations due to inflammatory mediators [43,44], are in line with some pathophysiological effects seen in obese patients regardless of whether or not they are at high altitude. In fact, it has been observed that obese individuals present an obesity-hypoventilation syndrome (OHS) accompanied by sleep disturbances, resulting in deep nocturnal oxygen desaturation and periodic apneic breathing [41,45] even at moderate elevations.…”
Section: Obesity and Acute Exposure To High Altitudementioning
confidence: 99%
See 1 more Smart Citation
“…However, the two major theories for the cause of HAPE, exacerbated pulmonary hypertension and/or capillary alterations due to inflammatory mediators [43,44], are in line with some pathophysiological effects seen in obese patients regardless of whether or not they are at high altitude. In fact, it has been observed that obese individuals present an obesity-hypoventilation syndrome (OHS) accompanied by sleep disturbances, resulting in deep nocturnal oxygen desaturation and periodic apneic breathing [41,45] even at moderate elevations.…”
Section: Obesity and Acute Exposure To High Altitudementioning
confidence: 99%
“…In addition, obese patients experience an increased inflammatory state, with the presence of inflammation mediators where increased levels of interleukin 6 have been described, along with other cytokines [48]. The above conditions are at the core of the current understanding of HAPE pathophysiology [44]. Therefore, the above mentioned factors are highly suggestive of a link between not only obesity and AMS but also between obesity and the development of HAPE.…”
Section: Obesity and Acute Exposure To High Altitudementioning
confidence: 99%
“…This enhanced hydrostatic stress causes dynamic changes in the permeability of the alveolar capillary barrier and induces a highpermeability noninflammatory lung edema. Previous report indicated that decreased nitric oxide release and enhanced endothelin levels following acute high-altitude exposure may be the major determinants of exaggerated hypoxic pulmonary vasoconstriction in HAPE-susceptible individuals [25]. In addition, other hypoxia-mediated changes of sympathetic nervous activity, endothelial function, and altered levels of other vasoactive mediators such as endothelin and angiotensin II may also contribute additionally to HAPE susceptibility.…”
Section: Pulmonary Vascular Systemmentioning
confidence: 98%
“…To date, 3 not mutually exclusive explanations have been put forward: (1) HAPE may initially arise from a subset of capillaries that branch off directly from the larger arteries and, thus, are unprotected when pulmonary artery pressures increases 17 ; (2) capillary pressures may rise because of concomitant pulmonary venoconstriction 18 ; and (3) heterogeneous vasoconstriction may result in uneven distribution of perfusion and local areas of high flow and pressure. 3 These concepts not only illustrate that drawing conclusions on local microhemodynamics from macrohemodynamic measurements can be problematic, but they also stress the potential role of pulmonary vasoconstriction in lung edema formation. A closer look at the data by Moon and colleagues may suggest a similar element of vasoconstriction in SIPE: Despite lower CO values, the transpulmonary pressure gradient (ie, the difference between mPAP and PAWP) tended to be higher in SIPE-susceptible subjects than in controls during both the dunk and subsequent submersed exercise.…”
Section: March 8 2016mentioning
confidence: 99%
“…Interestingly, SIPE shares common features with another form of pulmonary edema that is caused by strenuous exercise in an evolutionary nonphysiological habitat, namely high-altitude pulmonary edema (HAPE): Both SIPE and HAPE typically affect young healthy individuals, are triggered by strenuous exercise in a cold environment, resolve spontaneously after return to physiological conditions, yet will recur on reexposure in prone individuals. 2,3 At the pathological level, edema fluid in both SIPE and HAPE patients contains considerable amounts of red blood cells and high-molecular-weight proteins in the absence of markedly elevated inflammatory markers. 4,5 The pathophysiology of both diseases has long puzzled the field and hampered the development of effective counterstrategies, because their features tend to evade the traditional classification of pulmonary edema.…”
mentioning
confidence: 99%